Esterase patterns in species of the triatome bug Rhodnius - Tartarotti, E. [UNESP]; Neto, F. L. [UNESP]; Ceron, C. R. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
The aim of the present study was to analyse esterase patterns in three triatomine species of Rhodnius genus. Four loci, Est 1, Est 2, Est 3 and Est 4, were found. The corresponding enzymes were characterized as carboxylesterases (E.C. 3.1.1.1) or cholinesterases (E.C. 3.1.1.8) based on inhibitory experiments, using eserine sulphate, malathion, mercury chloride, p-chloromercuribenzoate (pCMB) and iodoacetamide. Low genetic variability was observed: Est 1, Est 2 and Est 3 were monomorphic in Rhodnius domesticus, Rhodnius robustus and Rhodnius neivai, whereas locus Est 4 was polymorphic in the first two species. The UPGMA analysis based on esterase genotypic frequencies indicated greater similarity between R. domesticus and R. robustus when compared with R. neivai. The present study expands our knowledge about genetic variability among triatomines and accords with the hypothesis that R. domesticus is a species derived from R. robustus.
Keywords: Rhodnius; esterase; genetic variability; Rhidniini; Triatominae